Activation of Wnt/Beta-Catenin Signaling Pathway as a Promising Therapeutic Candidate for Cerebral Ischemia/Reperfusion Injury - Mo, Zhizhun; Zeng, Zhongyi; Liu, Yuxiang; Zeng, Linsheng; Fang, Jiansong; Ma, Yinzhong (Frontiers in Pharmacology, 2022)
Stroke is one of the leading causes of mortality, and survivors experience serious neurological and motor behavioral deficiencies. Following a cerebral ischemic event, substantial alterations in both cellular and molecular activities occur because of ischemia/reperfusion injury. Wnt signaling is an evolutionarily conserved signaling pathway that has been manifested to play a key role in embryo development and function maintenance in adults. Overactivation of Wnt signaling has been investigated in previous cancer-based research studies. Recently, abnormal Wnt signaling activity has been observed in ischemic stroke, which is accompanied by massive Blood Brain Barrier (BBB) disruption, neuronal apoptosis, and neuroinflammation within the central nervous system (CNS). Significant therapeutic effects were observed after reactivating the adynamic signaling activity of canonical Wnt signaling in different cell types. To better understand the therapeutic potential of Wnt as a novel target for stroke, we reviewed the role of Wnt signaling in the pathogenesis of stroke in different cell types, including endothelial cells, neurons, oligodendrocytes, and microglia. A comprehensive understanding of Wnt signaling among different cells may help to evaluate its potential value for the development of novel therapeutic strategies based on Wnt activation that can ameliorate complications and improve functional rehabilitation after ischemic stroke.